Pengaruh motivasi terhadap keberhasilan usaha para pedagang di Pasar Parit di Kuala Tungkal Jambi - Wati, Laras; Dahmiri, Dahmiri; Indrawijaya, Sigit (Jurnal Dinamika Manajemen, 2021)
The main subjective of this research is to analyze the description of the motivation and success of the trader’s business and to analyze the influence of inspiration on the business success of traders in Pasar Part II Kuala Tungkal Jambi. The data used in this study is the primary data obtained by field research sourced from traders in Pasar Part II Kuala Tungkal Jambi as a sample. The sampling method used in this research is Purposive Random Sampling. Data were analyzed by descriptive quantitative analysis method. Data analysis tools use Simple Linear Regression. The study results found that the description of the trader’s motivation was in an outstanding category with a score of 4,42. Meanwhile, in the definition of the success of the trades business is in the excellent category with a score of 4,18. Based on the simple linear regression analysis, the regression coefficient of the motivation variable is 0,600 with a probability value below 0,05, which means that the motivation variable has a positive and significant effect on the business success of traders in Pasar Part II Kuala Tungkal Jambi.